Systemic Bias in Investor-State Dispute Settlement: Moral for the South Asian Host States - Ahmed, Forhad (Feni University Journal, 2026)
The International Investment Arbitration (IIA) method, known as the ISDS mechanism, is majorly divided into two devices: ICSID and non-ICSID arbitrations. The ICSID arbitration mechanism has been the most recognized dispute settlement mechanism formed by the ICSID convention. Non-ICSID arbitrations mainly comprise ways available other than ICSID arbitration, e.g., UNCITRAL, International Chamber of Commerce, London Court of International Arbitration, Stockholm Chamber of Commerce, etc. The organic nature of the International Investment regime has led to the progressive practice of dispute settlement mechanisms all over the world since the rise of Bilateral Investment Treaties (BIT) in the nineties. However, the scholarships and empirical studies show that the arbitration panels are not devoid of systemic or institutional biases. This conception is resulting in an era of resistance among the State parties to any BIT. This paper attempts to find out and justify the critique of institutional biases with the help of some secondary data and cases. In addition, the paper shall also include the approaches of South Asian countries as host states in foreign direct investment under specific BIT protection. FENI UNIVERSITY JOURNAL, 2024, 3(1), ISSN [2518-3869], PP. (223-234)